Evaluation of content usefulness and quality of YouTube™ videos as an information source for maxillofacial prosthesis - Rishu Koul; E. Mahesh Gowda; Guruprasada Upadhyay; Deepak Kalia; Kamal Verma (Wolters Kluwer Medknow Publications, 2024)
Background Social media platforms such as YouTube™ have become a widely popular source for information regarding health-related issues about medical and dental issues. The simplicity of online watching has concealed the drawback that these videos are not regularly reviewed or checked for their suitability as educational resources for dental professionals and students. Aim The purpose of the current study was to evaluate the content and quality of videos on YouTube™ regarding maxillofacial prosthesis as a source of learning by dental professionals. Materials and Methods Fifty-one videos satisfying inclusion criteria were watched and carefully reviewed. After that, the following data were recorded in terms of domain in maxillofacial prosthesis: number of views, likes, comments, subscribers of the channel, viewing rate, duration since upload of video, video length/duration, primary purpose of videos, video sources, target group of video, video content, video content usefulness score, modified discern instrument score, and global quality score. Results No misleading video about said topic was uploaded during the period. Only 5.9% of the YouTube™ videos on maxillofacial prostheses were good. Conclusions There is a dearth of good-quality videos and videos about maxillofacial prosthesis maintenance, which raises questions if maxillofacial videos on YouTube™ would be equally beneficial for patients.